2018
DOI: 10.9734/jammr/2018/43889
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Foreign Body in the Otolaryngology Service in Ado Ekiti

Abstract: Aims: To determine the prevalence, sociodemographic features, clinical presentation, patterns of foreign body impaction and management in our center. Study Design: A cross-sectional descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Literature also revealed a complication rate following FB removal of ear, nose, and upper esophageal was approximated between 9% and 25% 2,5,24 . In our study, associated complication of 18.35% of 169 children was within the acceptable range.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Literature also revealed a complication rate following FB removal of ear, nose, and upper esophageal was approximated between 9% and 25% 2,5,24 . In our study, associated complication of 18.35% of 169 children was within the acceptable range.…”
Section: Discussionsupporting
confidence: 60%
“…Males are predominantly presented with FB of ENT, as revealed by the present study. This finding is supported by different studies conducted in different countries 23‐26 . Contrary, other studies found insignificant differences 5,27 and female preponderance compared to male counterparts 10 …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation